2014
DOI: 10.1007/s00595-014-0937-x
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of oral feeding following upper gastrointestinal tumor surgery: a randomized controlled trial

Abstract: Early oral feeding after the surgical resection of esophageal and gastric tumors is safe, and is associated with favorable early in-hospital outcomes and a sooner return to physiological GI function and hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 23 publications
3
49
0
1
Order By: Relevance
“…Nevertheless, in line with other types of gastro-intestinal surgery, early initiation of oral intake has been investigated. Four comparative trials did not observe an increased morbidity rate and anastomotic leakage or aspiration incidents did not increase (30)(31)(32)(33). However, a large randomized controlled trial in which patients are monitored in a multicenter setting is needed to evaluate the potentially beneficial impact of early oral intake on postoperative recovery and quality of life in patients undergoing esophagectomy.…”
Section: Conclusion (Discussion and Recommendations)mentioning
confidence: 99%
“…Nevertheless, in line with other types of gastro-intestinal surgery, early initiation of oral intake has been investigated. Four comparative trials did not observe an increased morbidity rate and anastomotic leakage or aspiration incidents did not increase (30)(31)(32)(33). However, a large randomized controlled trial in which patients are monitored in a multicenter setting is needed to evaluate the potentially beneficial impact of early oral intake on postoperative recovery and quality of life in patients undergoing esophagectomy.…”
Section: Conclusion (Discussion and Recommendations)mentioning
confidence: 99%
“…Nutrition support is divided into enteral nutrition and parenteral nutrition, which is an important means to promote patients' rehabilitation. EEN refers to giving the enteral nutrition support within postoperative 6–24 h ( 8 ). Parenteral nutrition is to provide the body with an appropriate amount of three major nutrients, vitamins, electrolytes and water through parenteral pathways (usually through veins), but how to better improve the postoperative nutritional status and control blood glucose level of patients with gastric cancer complicated with diabetes mellitus is the focus and difficulty of the current research.…”
Section: Discussionmentioning
confidence: 99%
“…showed that early oral intake was safe and accelerated recovery. However, a substantial number of these patients underwent gastric surgery (34%), and the results were subjected to selection bias . Another study only included patients undergoing esophagectomy and showed faster postoperative gastric emptying …”
Section: Enhanced Recovery After Esophagectomymentioning
confidence: 99%
“…However, only a few patients who underwent an esophagectomy were included (2%). 163 A recent randomized trial by Mahmoodzadeh et al 164 showed that early oral intake was safe and accelerated recovery. However, a substantial number of these patients underwent gastric surgery (34%), and the results were subjected to selection bias.…”
Section: Enhanced Recovery After Esophagectomymentioning
confidence: 99%
See 1 more Smart Citation